Nepal Earthquake One Year On: Building a More Effective Relief Effort - Shrestha, Maxim (2016)
One year since the devastating Nepal earthquakes, the international relief effort holds lessons for future emergency response. While reconstruction efforts remain stifled, the immediate international relief operations experience offer some insights on how to deliver humanitarian assistance to mega disasters more effectively.